Elevated hsa_circRNA_101015, hsa_circRNA_101211, and hsa_circRNA_103470 in the Human Blood: Novel Biomarkers to Early Diagnose Acute Pancreatitis. (18th February 2020) - Liu, Chang; Zhu, Xuan; Niu, Xing; Chen, Lijie; Ge, Chunlin
Abstract : Objective . To explore potential biomarkers to accurately diagnose patients with acute pancreatitis (AP) at early stage and to auxiliary clinicians implement the best treatment options. Methods . We selected 3 patients with AP and 3 healthy controls for microarray analysis to obtain differentially expressed circular RNAs (circRNAs). To further verify the results of the microarray analysis, the six differentially expressed circRNAs were confirmed by quantitative polymerase chain reaction (qPCR). The diagnostic accuracy and sensitivity of differentially expressed circRNAs were assessed using the receiver operating characteristic (ROC) curve. A ceRNA network was constructed based on the 6 differentially expressed circRNAs. Results . There were 25 upregulated circRNAs and 26 downregulated circRNAs in the blood of patients with AP. Next, the qPCR verification results further confirmed three downregulated circRNAs, including hsa_circRNA_002532, has_circRNA_059665, and hsa_circRNA_104156, and three upregulated circRNAs including hsa_circRNA_101015, hsa_circRNA_101211, and hsa_circRNA_103470. Among them, hsa_circRNA_101015, hsa_circRNA_101211, and hsa_circRNA_103470 increased with the severity of the disease. ROC analysis showed that the three circRNA models show promise to diagnose AP. And a ceRNA network revealed that above six circRNAs could participate in complex regulated network. Conclusions . Elevated hsa_circRNA_101015, hsa_circRNA_101211, and hsa_circRNA_103470 could be used as novel biomarkers to diagnose AP patients.